Analisis Pengaruh Bahan Tambah Styrofoam Terhadap Kuat Tekan, Tarik Dan Lentur Pada Dinding Precast - Angga Winawan Hakim; Irwan Irwan; Melloukey Ardan (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2022)
Many new innovations have been found regarding wall structures that were previously conventional from bricks, which have been changed to more effective, lightweight and environmentally friendly materials. One alternative material that can be used is Styrofoam. This study aims to determine the compressive strength, split tensile strength and flexural strength of concrete when added with a mixture of Styrofoam with a percentage of 0%, 10% and 30% as well as to compare the mechanical behavior of the concrete mixture with Styrofoam and without Styrofoam and to analyze the test results as concrete. light weight according to SNI 03-2847-2002, then it can be designed as a precast wall used for partitions in high buildings, which meet the requirements in the demolding process. .In this study, data processing and analysis were carried out referring to SNI 1974-2011, SNI 03-2491-2002 and SNI 4431:2011. From the results of the analysis, it was found that the unit weight of 30% Styrofoam concrete was 1633.45 kg/m3, so it can be categorized as lightweight concrete which is smaller than 1900 kg/m3 (SNI 03-2847-2002). The compressive strength values with 0%, 10% and 30% Styrofoam volume at the age of 28 days respectively were 26.76 MPa (328.668 kg/cm2), 11.96 MPa (146.955 kg/cm2) and 10 ,02 MPa (123,100 kg/cm2). The value of the split tensile strength of concrete with 0%, 10% and 30% Styrofoam volumes at the age of 28 days in a row is 4.23 MPa, 3.45 MPa and 2.68 MPa, the maximum reduction to normal concrete is 36.64 % by volume 30% Styrofoam . The flexural strength values of concrete with 0%, 10% and 30% Styrofoam volumes at the age of 28 days, respectively, were 7.00 MPa, 6.59 MPa and 6.07 MPa and the percentage decrease in flexural strength with the addition of 10 Styrofoam volumes. % and 30% of normal concrete at 5.85% and 13.28%, respectively. So that the greater the volume of Styrofoam added to the concrete, the lower the value of compressive strength, split tensile and flexural strength produced.